2016
DOI: 10.1007/s00277-016-2739-2
|View full text |Cite
|
Sign up to set email alerts
|

Droplet digital PCR assay for quantifying of CALR mutant allelic burden in myeloproliferative neoplasms

Abstract: Dear Editor,Calreticulin (CALR) gene mutations (CALR mut ) have recently been discovered in about 20-35 % of patients affected by essential thrombocythemia (ET) and primary myelofibrosis (PMF) [1,2]. Several molecular assays have been developed to detect the most frequent CALR mut (type 1 consisting of a 52-bp deletion, and type 2 of a 5-bp insertion) [3,4]. All these techniques are useful for identifying CALR mut at the diagnosis, but they are not suitable for minimal residual disease (MRD) monitoring, since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In fact, in comparison with quantitative analog PCR, ddPCR has the potential to make quantitative analyses more reproducible, and precise quantitation might facilitate a variety of clinical tests. However, there are only few studies focused on the use of ddPCR in hematological malignancies [2126]. In a recent report, NOTCH1 mut were detected by NGS in 11% of monoclonal B cell lymphocytosis (MBL) and 13.4% of CLL Binet stage A patients [27]; moreover, this mutation was frequently observed at a low clonal level, particularly in MBL patients, and sequential analyses demonstrated that the NOTCH1 mut generally did not appear during the disease course, and that the mutational burden in positive cases remained stable over time.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in comparison with quantitative analog PCR, ddPCR has the potential to make quantitative analyses more reproducible, and precise quantitation might facilitate a variety of clinical tests. However, there are only few studies focused on the use of ddPCR in hematological malignancies [2126]. In a recent report, NOTCH1 mut were detected by NGS in 11% of monoclonal B cell lymphocytosis (MBL) and 13.4% of CLL Binet stage A patients [27]; moreover, this mutation was frequently observed at a low clonal level, particularly in MBL patients, and sequential analyses demonstrated that the NOTCH1 mut generally did not appear during the disease course, and that the mutational burden in positive cases remained stable over time.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR (qPCR) has been widely applied to nucleic acid-based diagnostic tests, but lack of standardization and a relatively poor accuracy have hindered its usefulness in some clinical applications. Droplet digital PCR (ddPCR) is a novel PCR-based technology that has already been successfully used for sensitive and reproducible detection of different pathogenetic variants [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the ddPCR technique can estimate the absolute quantitation of a molecular target without the need for calibrators or standard samples; moreover, it is especially powerful in MRD monitoring, as previously demonstrated. [10][11][12] We report for the first time the absolute quantitation of the BCR- ALL with t(8;22)/BCR-FGFR1 fusion is a very aggressive tumor characterized by rapid evolution, for which HSCT is strongly recommended; however, the recent use of tyrosine kinase inhibitors has expanded the treatment opportunities for these patients. 5 Our results demonstrate that ddPCR can not only provide quantitative data about the residual tumor burden, but also, as demonstrated for other hematologic malignancies, 11,12 it has adequate sensitivity to provide the chance of following disease response and modulating treatment, maybe preventing disease progression.…”
Section: Acute Lymphoblastic Leukemia With T(8;22)/bcr-fgfr1 Genementioning
confidence: 99%